PERBANDINGAN NILAI BAKAR BRIKET BATUBARA DAN BRIKET ARANG (CAMPURAN CANGKANG BINTARO (Cerbera Manghas) DAN BAMBU BETUNG (Dendrocalamus Asper) - Ida Febriana; Zurohaina Zurohaina; Sahrul Effendy (TEKNIKA: Jurnal Teknik, 2019)
Charcoal briquettes are smokeless fuels which are a type of solid fuel whose fly substance is made low enough so that the smoke generated on its utilization will not interfere with health. In this study charcoal briquettes were made from bintaro shell waste and betung bamboo using tapioca flour adhesives. This study aims to obtain the best quality sub-bituminous coal briquettes and coal briquettes. In this study the carbonization temperature used was 400ᵒC and the composition of raw materials for bintaro shells and betung bamboo was 50:50, the composition of raw materials for sub-bituminous coal and straw 90:10. The method used in this research is experiment or experimental method, with fuel value collection using ASTM D5865-03 standard. The results obtained from this study are for charcoal briquettes with 4000C carbonization temperature Inherent Moisture value of 1.91%, ash 2.29%, volatile matter 23.79%, fixed carbon 72.01% and calorific value 5878.7 kal / gr, and for coal briquettes obtained value Inherent Moisture 0.52%, ash 4.42%, volatile matter 17.98%, fixed carbon 77.08% and calorific value 7152.6 kal / gr. The fuel value of coal briquettes is greater than that of charcoal briquettes, but the combustion value of charcoal briquettes includes a good calorific value as an alternative energy source, and is in accordance with the SNI standard of 5000 kal / gr, even close to the Japanese standard 6000 cal / gr. Keywords: Bintaro, briquette, calorific value